Optimasi Dosis Pupuk Kalsium dan Magnesium pada Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Utama - Ningsih, Eltis Panca; ,, Sudradjat; ,, Supijatno (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
Oil palm is one of the important plantation crops in the plantation sector. Increased oil palm plantation area causes the need for the availability of oil palm seedlings in large quantities. Good quality oil palm seedlings were obtained through intensive maintenance especially fertilization. Fertilizers needed for the growth of oil palm seedlings include calcium and magnesium fertilizers. The objective of this experiment was to determine the optimum rates of calcium and magnesium fertilizer for oil palm seedling (Elaeis guineensis Jacq.). This experiment was conducted at Cikabayan Experimental Station, IPB Darmaga, Bogor, from December 2011 to November 2012. The experimental design used was factorial randomized block design with three replications. The first factor was Ca fertilizer rates i.e., 0, 5, 10, and 20 g CaCO3 plant-1. The second factor was Mg fertilizer rates, i.e., 0, 24, 48, and 96 g MgSO4 plant-1. The results showed that calcium affected stomatal density, whereas magnesium fertilizer affected morphological and physiological variables (stomatal density and chlorophyll content) of oil palm seedling. Based on the plant height and stem diameter, the recommended rate of magnesium fertilizer for 8 months oil palm seedlings in the main nursery was 58 g plant-1. This total rate should be applied at different amount every month from 1-8 month, at 2.0, 2.0, 8.0, 9.3, 8.8, 9.3, 9.4 and 9.3 g MgSO4 plants-1, respectively. The optimum rate of calcium fertilizer was not able to be determined in this research. Keywords: chlorophyll, leaf, morphology, physiology